Pengaruh Celebrity Endorsement Terhadap Purchase Intention Dengan Brand Image Sebagai Variabel Intervening (Study Kasus Mahasiswa Feb Unisma Angkatan 2016 Pembeli Shampoo Pantene) - Wiwin Mauliya; N. Rachma; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study was conducted to determine the effect of Celebrity Endorsement on purchase intention with brand image as an intervening variable in FEB UNISMA 2016 batch of shoppers pantene buyers. Which is located at Jl. MT. Haryono, No. 193, Dinoyo, Kec. Lowokwaru, Kota Malang, East Java. 65113. The method used is explanatory research which aims to explain the position of each variable and its influence between one variable with another variable, and the source of the data used is primary data by distributing linkert checker questionnaires to FEB UNISMA 2016 batch of buyers of Pantene shampoo . The sample calculation in this study uses the maholtra formula which produces 75 respondents. The results of this study indicate a significant direct effect on Celebrity Endorsement on brand image. Celebrity Endorsement of purchase intention. brand image of purchase intention. the indirect effect of Celebrity Endorsement variables, on purchase intention with brand image as an intervening variable.Keywords: celebrity endorsement, purchase intention, brand image